2021
DOI: 10.5430/wje.v11n2p56
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental Education Learning Activities Using Area-Based Learning in Khok Hin Lad Community Forest in Maha Sarakham, Thailand

Abstract: The purposes of this research were to study and compare knowledge about Khok Hin Lad community forest, environmental ethics, and environmental volunteers from learning activities of undergraduate students before and after activities, to study and compare knowledge about Khok Hin Lad community forest, environmental ethics, and environmental volunteers of undergraduate students with different gender and GPAs. The sample used in the research was 99 second-year undergraduate students in Environmental Education, Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These studies generally aimed to determine participants' environmental awareness and attitudes toward environmental education (Adanali & Mete, 2019;Dolenc Orbanic & Kovac, 2021;Durmus & Kinaci, 2021;Miyaji & Fukui, 2020;Molefe & Aubin, 2021;Ozonur, 2021). Some studies in the literature aimed to emphasize the effectiveness of specific environmental education program (Aksut & Aydin, 2021;Ayaz et al, 2021;Bardecki & McCarthy, 2020;Corpuz et al, 2022;Fettahlioglu, 2018;Hamalosmanoglu et al, 2020;Junkaew et al, 2021;Nogales-Delgado & Encinar Martín, 2019;Sims et al, 2020;Sookngam et al, 2021;Wongchantra et al, 2022aWongchantra et al, , 2022b. While others tried to show a relation between environmental education and other variables (Afacan, 2020;Chen et al, 2020;Demirkaya et al, 2020;Kaya et al, 2021;Kilicoglu, 2021;Onal, 2020;Ongon et al, 2021;Praimee et al, 2022).…”
Section: Conclusion Discussion and Recommandationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies generally aimed to determine participants' environmental awareness and attitudes toward environmental education (Adanali & Mete, 2019;Dolenc Orbanic & Kovac, 2021;Durmus & Kinaci, 2021;Miyaji & Fukui, 2020;Molefe & Aubin, 2021;Ozonur, 2021). Some studies in the literature aimed to emphasize the effectiveness of specific environmental education program (Aksut & Aydin, 2021;Ayaz et al, 2021;Bardecki & McCarthy, 2020;Corpuz et al, 2022;Fettahlioglu, 2018;Hamalosmanoglu et al, 2020;Junkaew et al, 2021;Nogales-Delgado & Encinar Martín, 2019;Sims et al, 2020;Sookngam et al, 2021;Wongchantra et al, 2022aWongchantra et al, , 2022b. While others tried to show a relation between environmental education and other variables (Afacan, 2020;Chen et al, 2020;Demirkaya et al, 2020;Kaya et al, 2021;Kilicoglu, 2021;Onal, 2020;Ongon et al, 2021;Praimee et al, 2022).…”
Section: Conclusion Discussion and Recommandationsmentioning
confidence: 99%
“…Furthermore, it was also found that, prospective science teachers' perceptions of environmental issues differed based on their selfefficacy beliefs at the end of the study. Furthermore, Junkaew et al (2021) discovered that students' average knowledge scores on Khok Hin Lad community forests, environmental ethics, and environmental volunteers were higher after learning activities than before the learning activities' statistical significance; and students of different genders did not differ in their knowledge of Khok Hin Lad community forests, environmental ethics, and environmental volunteers. The knowledge of the Khok Hin Lad community forest, environmental ethics, and environmental volunteers was the same for all students, regardless of GPA.…”
Section: Theme 3 Effectiveness Of Environmental Educationmentioning
confidence: 98%
“…After Students have academic achievement higher than before the study. And Junkaew, Wongchantra and Bunnaen (2021) found that Undergraduate students have knowledge about Khok Hin Lad Community Forest. (Huai Ka Kang Watershed Forest) after learning was higher than before learning.…”
Section: Discussionmentioning
confidence: 99%